Going wild a study on wildlife documentary genre shows in Philippine television - Ng, Christopher Cheng 1986-
"This thesis studies how the Wildlife Documentary genre in the Philippines evolved through the birth and first few years of existence of two shows, Born to be Wild and Matanglawin. With the advent of climate change, environmental problems began to attain more attention in the Philippines and thus in the Philippine media as well. This gave birth to two pioneering wildlife shows, Born to be Wild on GMA 7 and Matanglawin on ABS-CBn. In an effort to understand and give definition to the Wildlife Documentary genre in the Philippines, this thesis studied all available text with regards to both shows through newspaper articles, periodicals and online sources and finally, interviewed the producers of both shows to attain an in-depth story of how the shows were conceived and what they have become today. Due to the young nature of the genre, it was discovered that there is no clear cut definition that can be given to the Wildlife documentary genre in Philippine television because the genre is still continuing to evolve and change. There does not seem to be a wildlife documentary genre existing in the Philippine television today."